“Feels Good to Get Wet”: The Unique Affordances of Surf Therapy Among Australian Youth - McKenzie, Rebekah Jade; Chambers, Timothy P.; Nicholson-Perry, Kathryn; Pilgrim, Joel; Ward, Philip B. (Frontiers in Psychology, 2021)
Increasing prevalence rates of mental health problems among adolescents is an issue of growing concern. Surf therapy is a novel intervention that may provide tangible benefits to address this problem. Congruent with the ecological dynamics perspective (EDP), the existing research postulates that surf therapy yields psychological benefits in part due to the unique affordances of immersion in a blue space such as the ocean. Evidence worldwide has validated the use of surfing as a therapeutic mediator to achieve positive change, however, no such research has been conducted on Australian adolescents. The current study aimed to evaluate the impact of the Waves of Wellness (WOW) Foundation’s eight-week surf therapy program on mental health outcomes in Australian at-risk youth. The study employed a mixed-methods design to examine the experiences of participants. Nine adolescents (Mage = 14.9; SD = 1.2; 8 female) participated in the quantitative stage, with four completing the qualitative interview. Results indicated positive changes in resilience, self-esteem, social connectedness, and depressive symptoms post intervention, however, improvements were not maintained at follow-up. Participants unanimously agreed that the program normalised their experiences with mental health through the unique leaning environment and fostered personal growth through mastery experiences and the development of healthy relationships. The EDP provided the most compelling explanation of the results denoting that benefits arise from the reciprocal relationship between individual, task, and environment. Despite the small and heterogenous sample, the findings provided preliminary evidence of the efficacy of surf therapy among Australian youth and offer a potential starting point for further research utilising larger more diverse samples.